Molecular simulation of interfacial reaction between TiAl alloy melts and different coatings - Yan-wei Sui; Cheng Cheng; Kun Feng (China Foundry, 2017)
The effect of coatings (Y2O3, ZrO2 and Al2O3) on the interfacial reaction of TiAl alloys was studied with molecular dynamics. The binding energy of coatings and the diffusion process of oxygen in the melt were simulated, and then the simulation results were compared with the experimental results. The simulation results indicate that for each of the three simulated coatings, inordinate interfacial reactions have occurred between the coating and the melt. The binding energy results show that Y2O3 has the best stability and is the most difficult to break down. ZrO2 has the greatest decomposition energy and is the easiest to break down in the melt. Besides, the molecular dynamics indicate that the diffusion coefficient of the oxygen atom in Al2O3 is larger than that in the other two coatings, indicating that oxygen diffusion in Al2O3 is the fastest at a given temperature. The experimental results show that the oxygen concentration of the melt with Al2O3 coating is the highest, and the oxygen diffusion is of similar magnitude to the simulation values, from which the conclusion can be obtained that the oxygen concentration is significantly influenced by the coating materials.